The Revelance of Günter Wallraff‘s Investigative Journalism Problematics - Tubys, Lukrecijus (Žurnalistikos tyrimai, 2017)
This paper provides analysis of investigative journalism climate in Lithuania and possibilities weather Günter Wallraff’s investigative methods could be applied in this country. Due to that author interviewed various experts of media, human rights and ethics. They shared their opinion about what is the value of investigative journalism, what topic should be investigated the most, what are the most famous investigative journalists in Lithuania, could methods of G. Wallraff be used in this country and so on. Article also answers who G. Wallraff is and what he is famous for as well as gives different definitions of what investigative journalism is, according to media scholars. In addition to this, paper presents a short brief of history of investigative journalism in Lithuania and in the world and emphasizes the major development differences. Article also gives an interpretation why investigative journalism is lacking in Lithuania nowadays and what is needed in order to strength it.